2017
DOI: 10.5812/numonthly.44278
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality in Patients Undergoing Long-term Hemodialysis Using the Pittsburgh Sleep Quality Index

Abstract: Background: Sleep disturbances are common among uremic patients. However, limited data are available on predictors of the quality of sleep in this population. Objectives: This study aimed to assess the quality of sleep in patients undergoing hemodialysis and investigate its predictors. Methods: In this cross-sectional study, 197 patients on maintenance hemodialysis were consecutively included from three medical centers in Shiraz, southern Iran. They completed the Pittsburgh sleep quality index. Serum calcium, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
(40 reference statements)
1
12
1
Order By: Relevance
“…Our participants' median score for PSQI was 8 (5)(6)(7)(8)(9)(10)(11)(12), which is similar to a study in Pakistan, 8.0 [7.0-10.0] [25]. Therefore, there is a similarity between the results we have come up with and many other previous studies [4,[30][31][32][33][34][35]. For example, 63% of HD patients were poor sleepers, as reported in a Turkish study in 2014 [34].…”
Section: Discussionsupporting
confidence: 87%
“…Our participants' median score for PSQI was 8 (5)(6)(7)(8)(9)(10)(11)(12), which is similar to a study in Pakistan, 8.0 [7.0-10.0] [25]. Therefore, there is a similarity between the results we have come up with and many other previous studies [4,[30][31][32][33][34][35]. For example, 63% of HD patients were poor sleepers, as reported in a Turkish study in 2014 [34].…”
Section: Discussionsupporting
confidence: 87%
“…No significant relationships were found between dialysis shift and sleep quality. Some similar studies on hemodialysis patients by Trbojević-Stanković et al (2014); Firoz, Shafipour, Jafari, Hosseini, and Charati (2015); Chang and Yang (2011); and Mehrabi, Sarikhani, and Roozbeh (2017) did not find significant relationships between sleep quality and hemodialysis shift and most of their hemodialysis patients suffered from poor sleep quality. But Menon et al (2015) reported 67% of their hemodialysis patients suffered from poor quality of sleep, which was significantly correlated with the morning dialysis schedule.…”
Section: Discussionmentioning
confidence: 90%
“…Einollahi, Motalebi, Rostami, Nemati, andSalesi (2015) andHydarinia Naieni et al (2016) reported that sleep quality has a significant relationship with age, female gender, marital status, number of children, and employment in hemodialysis patients. The results of a study by Mehrabi et al (2017) indicated that low quality sleep has a significant relationship with BMI and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences are growing that hyperphosphatemia was associated with poor sleep quality [ 20 , 21 , 92 , 93 ], despite inconsistencies existing [ 24 ]. While the presence of hyperphosphatemia-related pruritus could be the mediating factor for poor sleep quality [ 20 ], to the best of our knowledge, there is no clear mechanism of how poor sleep quality may influence serum phosphate level among the dialysis population.…”
Section: Discussionmentioning
confidence: 99%